2015
DOI: 10.1016/j.bone.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing time-lapse micro-CT-correlated bisphosphonate binding kinetics and soft tissue-derived input functions to differentiate site-specific changes in bone metabolism in vivo

Abstract: The turnover of bone is a tightly regulated process between bone formation and resorption to ensure skeletal homeostasis. This process differs between bone types, with trabecular bone often associated with higher turnover than cortical bone. Analyses of bone by micro-computed tomography (micro-CT) reveal changes in structure and mineral content, but are limited in the study of metabolic activity at a single time point, while analyses of serum markers can reveal changes in bone metabolism, but cannot delineate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The bone-targeting delivery could then result in a local enrichment of the duplex drug in the skeleton due to its high affinity of the BP residue for the hydroxylapaptite of bone [14]. It has also been recently shown that bisphosphonates preferentially localize to regions of high bone turnover, suggesting bisphosphonate duplex drugs may preferentially enrich to the metabolically active tumorburdened regions of the skeleton [24]. It is well known that the P-C-P function of BPs is the prerequisite for the bonetargeting activity, whereby the intensity of the antiosteoclastic activity and the cytotoxic potential is exclusively dependent upon the side chain [25].…”
Section: Discussionmentioning
confidence: 97%
“…The bone-targeting delivery could then result in a local enrichment of the duplex drug in the skeleton due to its high affinity of the BP residue for the hydroxylapaptite of bone [14]. It has also been recently shown that bisphosphonates preferentially localize to regions of high bone turnover, suggesting bisphosphonate duplex drugs may preferentially enrich to the metabolically active tumorburdened regions of the skeleton [24]. It is well known that the P-C-P function of BPs is the prerequisite for the bonetargeting activity, whereby the intensity of the antiosteoclastic activity and the cytotoxic potential is exclusively dependent upon the side chain [25].…”
Section: Discussionmentioning
confidence: 97%
“…We would determine the effect of knee loading to collateral circulation around the femoral head in the further study. In bone homeostasis, balance between bone formation by osteoblasts and bone resorption by osteoclasts is required [46]. We conducted in vitro assays and evaluated the role of knee loading in the fate of bone marrow-derived cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cortical bone and trabecular bone show different metabolic behaviors in many physiological and pathological processes, such as glycation, pharmacokinetics, and their response to diet and implant insertion . The difference in metabolic activity is best demonstrated by their different remodeling process, which has significant clinical relevance for the treatment of osteoporosis . Trabeculae, as thin plates, have a low matrix volume and a large surface area; therefore, signals within the matrix can readily traverse the matrix volume to locate a surface to initiate trabecular remodeling.…”
mentioning
confidence: 99%
“…Trabeculae, as thin plates, have a low matrix volume and a large surface area; therefore, signals within the matrix can readily traverse the matrix volume to locate a surface to initiate trabecular remodeling. By contrast, cortical bone has a large matrix volume and a small surface area; therefore, signals deep within the matrix may not locate a surface as readily to initiate remodeling, allowing for the accumulation of microdamage, particularly in interstitial bone that is less remodeled . Furthermore, different mechanoresponsiveness levels in cortical and trabecular bone lead to different bone formation abilities in response to the mechanical load on the bone .…”
mentioning
confidence: 99%